Morphometry and lengthwise relationship of Megalaspis cordyla(Linnaeus, 1758) from Mumbai coast - Saker, Yassar; Jaiswar, A K; Chakraborty, S K; Swamy, R P (Indian Journal of Fisheries, 2011)
Morphometry and lengthwise relationship of Megalaspis cordyla(Linnaeus, 1758) from Mumbai coast